A Case Series: Non-vascularized Autologous Fibular Graft in the Treatment of Major Segmental Bone Defect after Post-traumatic at Diaphyseal Femur - Siregar, Hidayat; Gunawan, Rahmad; Fitriadi, Didi (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND In the management of bony defects, autologous bone grafts can be used as the mechanical structure for reconstruction to restore aesthetics and function, Non-vascularized autologus fibular graft are often used to the treat large post traumatic defects caused by high-energy trauma with open fracture and nonunion cases for 1st and 2nd cases. Here we would like to present a 16-year-old woman and a 37-year-old man patients of major bone defect at the right femoral shaft region using 9 cm and 10 cm non-vascularized fibular autogenous grafts. OBJECTIVE The purpose of this case report was to determine the effectiveness of non-vascularized autologus fibular graft for major bone defect at the regio femoral shaft for the reconstruction of post traumatic case. MATERIAL AND METHODS We treat post traumatic of the major bone defect at the regio femoral shaft with 9 cm and 10 cm femoral non-vascularized autologus fibular graft and fixed by a limited contact dynamic compression plate and femoral locking plate methode by routine phisioteraphy. RESULTS The Patient have a good result with good functional outcome after open reduction internal fixation (ORIF) and using a non-vascularized autologus fibular graft for treating the major bone defect after post traumatic femoral shaft fracture. CONCLUSION Complete and comperhensive open reduction internal fixation (ORIF) with autologous non- vascularized fibular graft, stabilized fracture by limited contact dynamic compression plate for 1st patient and femoral locking plate for 2nd patient allowing with an early rehabilitation is an acceptable, Phisioteraphy and early mobilisation resulting better outcome for the patient, all of this are less expensive, can be accepted at the hospitals that limited facilities and health professionals for professional subspeciality and widely reproducible option to manage bone defects in open shaft femoral fractures to achieving union, preserving length and motion with no donor site morbidity, giving patients good functional outcome and radiologic result. KEYWORDS Major bone defect, non-vascularized autologus fibular graft, autologous bone grafts, femoral shaft fracture, Open Fracture, Muskuloskeletal Reconstruction, Bone Loss, Nonunion.